Better to burn out than it is to rust: coordinating cellular redox states during aging and stress. (31st July 2015) - Rongo, Christopher
<x xml:space="preserve">Abstract</x> Both the protein homeostasis (proteostasis) and the oxidation/reduction (redox) environment of the cell play critical roles in disease‐ and age‐associated decline, yet the relationship between the two remains mysterious. In this issue of The EMBO Journal, Kirstein et al (2015) show that both the cytosol and the ER shift their redox states in response to proteotoxic stress and that stress in one compartment can alter redox state in the other. Moreover, proteotoxic stress can induce changes in redox state across tissues, suggesting that an organism‐wide surveillance mechanism modulates cellular redox environment.